2010
DOI: 10.1111/j.1468-1293.2009.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐medically supervised treatment interruptions among participants in a universally accessible antiretroviral therapy programme

Abstract: We examined clinical outcomes, patient characteristics and trends over time of non-medically supervised treatment interruptions (TIs) from a free-of-charge antiretroviral therapy (ART) programme in British Columbia (BC), Canada. MethodsData from ART-naïve individuals 18 years old who initiated triple combination highly active antiretroviral therapy (HAART) between January 2000 and June 2006 were analysed. Participants having 3 month gap in HAART coverage were defined as having a TI. Cox proportional hazards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 23 publications
9
40
1
Order By: Relevance
“…It has been found that women have reduced uptake of ART [24,25], higher incidence of treatment interruption [26,27], treatment discontinuation [28], and viral rebound after initial suppression than men [8,29,30]. Mediating factors that may influence these findings include increased development of depressive symptoms in women [9•, 31, 32], reduced disclosure of serostatus [33], and support from interpersonal relationships [21].…”
Section: Introductionmentioning
confidence: 95%
“…It has been found that women have reduced uptake of ART [24,25], higher incidence of treatment interruption [26,27], treatment discontinuation [28], and viral rebound after initial suppression than men [8,29,30]. Mediating factors that may influence these findings include increased development of depressive symptoms in women [9•, 31, 32], reduced disclosure of serostatus [33], and support from interpersonal relationships [21].…”
Section: Introductionmentioning
confidence: 95%
“…While some studies have found no association of sex with response to ART, [17][18][19] others have suggested that women have superior virologic, immunologic, and clinical outcomes compared with men. [20][21][22][23][24] It is unknown if this is attributable to biological factors, such as pharmacokinetics, 25,26 or behavioral or structural factors, such as adherence 27 or access to or quality of care. 28 Despite evidence that there may be sex differences in both the course of HCV disease and the response to ART among HIV-infected individuals, there have been no studies examining HIV-associated outcomes with respect to both sex and HCV status over time.…”
Section: Introductionmentioning
confidence: 99%
“…The regimens are often complicated and can include varying dosing schedules, dietary restrictions, and adverse effects [4].Consistently high levels of adherence are necessary for reliable viral suppression [5] and prevention of resistance [6], disease progression, and death [7]. Even though antiretroviral therapy is the single most dramatic development yet in the treatment of HIV/ AIDS, many have been described as inconsistent with their treatment regimens [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies reported that a number of patients took less than 95% of antiretroviral therapy [8,9]. A study done in southwest Ethiopia in 2008 found that the prevalence of non adherence to antiretroviral therapy was 21% [15].…”
Section: Introductionmentioning
confidence: 99%